UPAYA PENINGKATAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN E-LKPD BERBASIS CANVA PADA PESERTA DIDIK KELAS IV SDN 10 KOTO BARU. - Loly Ramadhani (Jurnal Dharma PGSD, 2025)
This research was conducted in two cycles as Classroom Action Research (CAR). ELKPD designed using Canva became the main focus because of its ability to improve the achievement of fourth-grade students at SDN 10 Koto Baru. The research subjects consisted of eleven fourth-grade students. At the end of each cycle, data was collected through observation and learning outcome tests. The collected data was then analyzed quantitatively. The research results showed an increase in student learning outcomes after using Canva-based E-LKPD. In the first cycle, the average score reached 70 with a learning completion rate of 45%. This figure increased to 81.8% in the second cycle with an average score of 85.4. The research concluded that teachers can make learning more interesting and relevant by utilizing digital teaching materials such as ELKPD created using Canva.